Green light organic electroluminescent device and display device comprising the same

By using P-type and N-type materials with specific structures in OLED green light devices, the thermal stability and molecular spacing of molecules are improved, and the problems of poor high temperature reliability and short life in the prior art are solved, and high efficiency and long life are achieved Green light organic electroluminescent devices.

CN113991044BActive Publication Date: 2025-01-10BOE TECHNOLOGY GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111273033.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-01-10
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

The existing OLED green light devices have poor high temperature reliability, short life and low luminous efficiency.

Method used

Using P-type and N-type materials with specific structures as the main material of the luminescent layer, the thermal stability of the molecules and the separation of HOMO and LUMO energy levels are improved, and the P-type and The molecular spacing of N-type materials improves the efficiency and life of the device.

Benefits of technology

Green light organic electroluminescent devices with high fluorescence quantum yield, low voltage and long life are achieved, which significantly improves the efficiency and life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113991044B_ABST
    Figure CN113991044B_ABST
Patent Text Reader

Abstract

The present invention discloses a green organic electroluminescent device and a display device comprising the same. The green organic electroluminescent device comprises a light-emitting layer, wherein the light-emitting layer comprises a main material; the main material comprises a P-type material and an N-type material; wherein at least the N-type material comprises a compound having a structural formula shown in the following formula I and / or formula II. The present invention can at least partially solve the problems of poor high temperature reliability, short life and low luminous efficiency of OLED green light devices in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of display technology, and more specifically, to a green light organic electroluminescent device and a display device comprising the organic electroluminescent device. Background Art

[0002] In the mass-produced OLED devices today, green light devices are phosphorescent devices. The green light host material is a premixed material, including a hole-type host (P-type) and an electron-type host (N-type). The green light doping material is a phosphorescent doping material. Under photoexcitation or electroexcitation, excitons are formed on the host material, and through energy transfer, the excitons are transferred from the host to the guest (dopant), and then emit light through the dopant radiation transition. The host materials of existing green light devices have poor thermal stability, poor long-term evaporation stability of the material and poor high-temperature reliability of the device, and a low lifespan; in addition, the molecular design is unreasonable, the T1 value is low, and it is easy to cause the excitons to be transferred from the guest to the host in reverse, reducing the exciton utilization rate. Summary of the invention

[0003] In view of the defects in the prior art, the present invention provides a green organic electroluminescent device and a display device comprising the green organic electroluminescent device, which can at least partially solve the problems of poor high temperature reliability, short life and low luminous efficiency of OLED green light devices in the prior art.

[0004] In a first aspect, the present invention provides a green organic electroluminescent device, comprising a light-emitting layer, wherein the light-emitting layer comprises a host material;

[0005] The main material includes P-type material and N-type material; wherein,

[0006] At least the N-type material comprises a compound having a structural formula shown in Formula I and / or Formula II below:

[0007]

[0008] in:

[0009] R0 is selected from C or N;

[0010] R3, R4 and R a are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl, and R3, R4 and R a At least one of them is adamantyl or an adamantyl derivative;

[0011] L3 is selected from a single bond, an adamantyl group, a C6 to C30 aryl group or a heteroaryl group.

[0012] Optionally, the compound having the structural formula shown in Formula I or Formula II has a specific structure of one of the following formulas:

[0013]

[0014] in:

[0015] R3, R4, and R5 are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl, and at least one of R3, R4, and R5 is adamantyl or adamantyl derivative;

[0016] R6, R7, and R8 are each independently selected from C6 to C30 aryl or heteroaryl;

[0017] L3 and L4 are each independently selected from a single bond, an adamantyl group, a C6 to C30 aryl group or a heteroaryl group.

[0018] Optionally, the adamantyl derivative is an adamantyl substituted with a C6 to C30 aryl or heteroaryl group.

[0019] Optionally, the C6 to C30 aryl groups, when present at each occurrence, are independently selected from phenyl, biphenyl, triphenylene or fluorenyl; and / or

[0020] The C6 to C30 heteroaryl group, at each occurrence, is independently selected from dibenzofuranyl or thienyl.

[0021] Optionally, the specific structure of the compound is one of the following formulas:

[0022]

[0023]

[0024] Optionally, the molecular distance between the P-type material and the N-type material is above.

[0025] Optionally, the P-type material has a structure as shown in the following formula III:

[0026]

[0027] in:

[0028] R1 and R2 are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl; L1 and L2 are each independently selected from a single bond, C6 to C30 aryl or heteroaryl.

[0029] n1 and n2 are independently selected from 0 or 1.

[0030] Optionally, the P-type material has a structure shown in one of the following formulae III-1 to III-3:

[0031]

[0032]

[0033] Optionally, the green organic electroluminescent device further comprises an electron blocking layer disposed adjacent to the light-emitting layer, and the material of the electron blocking layer has a structure shown in the following formula IV:

[0034]

[0035] Among them, R9, R 10 , R 11 Each is independently selected from one of adamantyl, spirofluoreneadamantyl, fluorenyl, dimethylfluorenyl, diphenylfluorenyl, spirofluorenyl, phenyl, biphenyl, diphenylfuranyl, thienyl, spirooxy and thioxanthenyl.

[0036] Optionally, the HOMO energy level of the N-type material is 5.4-5.8 eV, and the LUMO energy level is 2.2-2.6 eV;

[0037] The HOMO energy level of the P-type material is 5.3-5.6 eV, and the LUMO energy level is 2.0-2.4 eV;

[0038] The T1 energy level of the N-type material is 2.2-2.8 eV, and the T1 energy level of the P-type material is 2.5-3.1 eV; and

[0039] The difference between the T1 energy level of the P-type material and the T1 energy level of the N-type material is more than 0.1 eV.

[0040] Optionally, the HOMO energy level of the material of the electron blocking layer is 5.3-5.7 eV, and the LUMO energy level is 2.2-2.7 eV; the T1 energy level of the material of the electron blocking layer is 2.5-3.1 eV; and

[0041] The T1 energy level of the material of the electron blocking layer is greater than the T1 energy level of the P-type material.

[0042] Optionally, the glass transition temperature of the N-type material is 80-140° C., the glass transition temperature of the P-type material is 80-140° C., and the difference between the glass transition temperatures of the N-type material and the P-type material is less than 30° C.

[0043] Optionally, the molar ratio of the P-type material to the N-type material is 5:5-7:3.

[0044] In a second aspect, the present invention provides a display device, which includes any one of the above-mentioned electroluminescent devices.

[0045] The beneficial effects of the present invention are as follows:

[0046] The green light organic electroluminescent device in the present invention is a green light device, which has a high fluorescence quantum yield, and due to the introduction of the compound of the structural formula shown in Formula I and / or Formula II in the main material of the light-emitting layer, the thermal stability of the molecule can be improved, and the introduction of the adamantyl group or the adamantyl derivative in the N-type material completely separates the HOMO and LUMO of the molecule, thereby improving the T1 of the molecule; thereby improving the efficiency and life of the device; in addition, due to the introduction of the adamantyl group or the adamantyl derivative in the main material of the light-emitting layer, the molecular distance between the P-type material and the N-type material is significantly increased, thereby further improving the efficiency of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0048] Figure 1 The figure shows the relationship between the fluorescence quantum yield of the light-emitting film and the molar ratio of the P-type material / N-type material in the prior art. DETAILED DESCRIPTION

[0049] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0050] The embodiments of the present invention provide a green organic electroluminescent device and a display device including the green organic electroluminescent device to solve the problems of low efficiency, poor thermal stability and short life of the existing OLED green light devices.

[0051] An embodiment of the present invention provides a green light organic electroluminescent device, comprising a light emitting layer, wherein the light emitting layer comprises a host material;

[0052] The main material includes P-type material and N-type material; wherein,

[0053] At least the N-type material comprises a compound having a structural formula shown in Formula I and / or Formula II below:

[0054]

[0055] in:

[0056] R0 is selected from C or N;

[0057] R3, R4 and R a are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl, and R3, R4 and R a At least one of them is adamantyl or an adamantyl derivative;

[0058] L3 is selected from a single bond, an adamantyl group, a C6 to C30 aryl group or a heteroaryl group.

[0059] In some embodiments, the C6 to C30 aryl group, at each occurrence, is independently selected from phenyl, biphenyl, triphenylene or fluorenyl.

[0060] In some embodiments, each occurrence of the C6 to C30 heteroaryl is independently selected from dibenzofuranyl or thienyl.

[0061] In some embodiments, the adamantyl derivative is a C6 to C30 aryl or heteroaryl substituted adamantyl.

[0062] In the above technical solution, the structure of the N-type material contains adamantyl or adamantyl derivative, which can completely separate the HOMO and LUMO in the molecular structure of the material, thereby improving the T1 of the molecule; thereby improving the efficiency and life of the green light organic electroluminescent device.

[0063] In some embodiments, the compound having the structural formula shown in Formula I or Formula II has a specific structure in one of the following formulas:

[0064]

[0065] in:

[0066] R3, R4, and R5 are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl, and at least one of R3, R4, and R5 is adamantyl or adamantyl derivative;

[0067] R6, R7, and R8 are each independently selected from C6 to C30 aryl or heteroaryl;

[0068] L3 and L4 are each independently selected from a single bond, an adamantyl group, a C6 to C30 aryl group or a heteroaryl group.

[0069] In some preferred embodiments, the specific structure of the compound is one of the following formulas:

[0070]

[0071] In some embodiments, the molecular distance between the P-type material and the N-type material is The higher the molecular distance between the two, the higher the dispersion of the N-type molecules in the host material, which can further improve the luminous efficiency of the green organic electroluminescent device.

[0072] In this embodiment, it is found that the selection and matching of P-type materials and N-type materials first affect the fluorescence quantum yield (PLQY) of the host. The ΔEst of the host will affect whether the energy transfer from the host to the guest is Forster or Dexter; and the host material will affect the injection of electrons and holes from the adjacent functional layer to the light-emitting layer, affecting the turn-on voltage and operating voltage of the device; the ratio of P-type materials and N-type materials will affect the electron mobility and hole mobility of the light-emitting layer, and then affect the exciton recombination area, which has a great impact on the voltage efficiency and life of the device. Therefore, optimizing the combination of P-type materials and N-type materials in the host material is crucial to reduce the voltage and improve the efficiency and life of green phosphorescent devices.

[0073] In some embodiments, the P-type material has a structure as shown in Formula III below:

[0074]

[0075] in:

[0076] R1 and R2 are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl;

[0077] L1 and L2 are each independently selected from a single bond, a C6 to C30 aryl group or a heteroaryl group.

[0078] n1 and n2 are independently selected from 0 or 1.

[0079] In this technical solution, both the P-type material and the N-type material have adamantane structure, which will significantly increase the molecular distance between the P-type material and the N-type material. This is equivalent to a higher degree of dispersion of the N-type molecules under the same P / N molar ratio, which can further improve the luminous efficiency of the green organic electroluminescent device.

[0080] In some preferred embodiments, the P-type material has a structure shown in one of the following formulae III-1 to III-3:

[0081]

[0082]

[0083] In some embodiments, the light-emitting layer further includes a green light doping material, and exemplary green light doping materials include but are not limited to: In the light-emitting layer, the mass percentage of the green light doping material is 6-14wt%.

[0084] In some embodiments, the green organic electroluminescent device further comprises an electron blocking layer disposed adjacent to the light-emitting layer, and the material of the electron blocking layer has a structure shown in the following formula IV:

[0085]

[0086] Among them, R9, R 10 , R 11 Each is independently selected from one of adamantyl, spirofluoreneadamantyl, fluorenyl, dimethylfluorenyl, diphenylfluorenyl, spirofluorenyl, phenyl, biphenyl, diphenylfuranyl, thienyl, spirooxy and thioxanthenyl.

[0087] In the embodiment of the present invention, the green organic electroluminescent device having the electron blocking layer shown in the above structural formula has low voltage, high efficiency and long life.

[0088] In some embodiments, the HOMO energy level of the N-type material is 5.4-5.8 eV, and the LUMO energy level is 2.2-2.6 eV;

[0089] The HOMO energy level of the P-type material is 5.3-5.6 eV, and the LUMO energy level is 2.0-2.4 eV;

[0090] The T1 energy level of the N-type material is 2.2-2.8 eV, and the T1 energy level of the P-type material is 2.5-3.1 eV; and

[0091] The difference between the T1 energy level of the P-type material and the T1 energy level of the N-type material is more than 0.1 eV.

[0092] In some embodiments, the HOMO energy level of the material of the electron blocking layer is 5.3-5.7 eV, and the LUMO energy level is 2.2-2.7 eV;

[0093] The T1 energy level of the material of the electron blocking layer is 2.5-3.1 eV; and

[0094] The T1 energy level of the material of the electron blocking layer is greater than the T1 energy level of the P-type material.

[0095] In some embodiments, the glass transition temperature of the N-type material is 80-140°C, the glass transition temperature of the P-type material is 80-140°C, and the difference between the glass transition temperatures of the N-type material and the P-type material is less than 30°C.

[0096] In some embodiments, the molar ratio of the P-type material to the N-type material is 5:5-7:3. In this case, the green organic electroluminescent device obtained has better luminous efficiency.

[0097] It can be understood that the green organic electroluminescent device of the present invention includes a substrate, and an anode, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, and a cathode arranged in sequence on the substrate.

[0098] The green organic electroluminescent device in the present disclosure is a phosphorescent device.

[0099] Yet another embodiment of the present invention provides a display device, which includes the green organic electroluminescent device described in the above embodiment.

[0100] The technical solution of the present invention is described below in conjunction with some specific embodiments:

[0101] It should be noted that in the following embodiments and comparative examples, some of the material structures used are as follows:

[0102] P-type material:

[0103]

[0104] N-type materials:

[0105]

[0106] Doping materials:

[0107]

[0108] Electron blocking layer materials:

[0109]

[0110]

[0111] The physical properties of the above materials are shown in Table 1 below.

[0112] Table 1

[0113] Material HOMO / eV LUMO / eV T1 / eV Tg / ℃ P1 5.43 2.11 2.69 108 P2 5.47 2.14 2.67 116 P3 5.41 2.10 2.65 115 P4 5.44 2.08 2.66 96 P5 5.42 2.12 2.64 108 P6 5.46 2.14 2.62 106 N1 5.51 2.36 2.52 120 N2 5.54 2.31 2.54 116 N3 5.56 2.54 2.55 118 N4 5.54 2.44 2.54 109 N5 5.58 2.51 2.58 108 N6 5.62 2.49 2.56 112 G’1 5.62 2.48 2.54 126 G’2 5.58 2.52 2.58 128 G’3 5.56 2.54 2.56 122 G’4 5.48 2.55 2.55 112 G’5 5.54 2.52 2.59 118 G’6 5.60 2.63 2.57 114

[0114] In the above materials, the molecular distances and schematic structures of P1 and N1, P2 and N2, P3 and N3, P4 and N4, P5 and N5, and P6 and N6 are shown in Table 2 below.

[0115] Table 2

[0116]

[0117]

[0118] Synthesis example 1:

[0119] Synthesis of intermediate a-1:

[0120]

[0121] 1-adamantanol (50.0 g, 328.4 mmol), bromobenzene (51.6 g 328.4 mmol), and dichloromethane (DCM, 500 mL) were added to a round-bottom flask, cooled to -5 to 0°C under nitrogen protection, trifluoromethanesulfonic acid (73.9 g, 492.6 mmol) was added dropwise at -5 to 0°C, and the mixture was stirred for 3 h; deionized water (300 mL) was added to the reaction solution and washed until pH = 7, dichloromethane (100 mL) was added for extraction, the organic phases were combined, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure; the crude product was purified by silica gel column chromatography using n-heptane as the mobile phase to obtain a white solid intermediate a-1 (52.6 g, 55%)

[0122]

[0123] Indolo[2,3-A]carbazole (20.0 g, 78.03 mmol), intermediate a-1 (22.72 g, 78.03 mmol), cuprous iodide CuI (2.97 g, 15.60 mmol), 1,10-phenanthroline (5.62 g, 31.18 mmol), potassium carbonate K2CO3 (23.72 g, 171.67 mmol), 18-crown ether-6 (2.06 g, 7.80 mmol) were added into a three-necked flask, and dried DMF (200 mL) solvent was added. Under nitrogen protection, the temperature was raised to 150°C, and the temperature was maintained and stirred for 18 hours; cooled to room temperature, stirring was stopped, the reaction solution was washed with water, and the organic phase was separated, dried over anhydrous magnesium sulfate, and the solvent was removed under reduced pressure to obtain a crude product; the crude product was purified by silica gel column chromatography using dichloromethane / n-heptane as the mobile phase to obtain a white solid product intermediate a-2 (19.6 g, 54%).

[0124]

[0125] In a degassed nitrogen-substituted three-necked flask, add 55% sodium hydride NaH (0.92 g, 21.4 mmol) and 100 ml of dehydrated DMF, stir under nitrogen flow, and cool to 0°C. At 0°C, add the dehydrated DMF solution of intermediate a-2 (10.0 g, 21.4 mmol). After the addition, stir for 1 hour, and then add the DMF solution of 2-bromo-4,6-diphenyl-[1,3,5]triazine (6.6 g, 21.4 mmol). After the addition, stir for 3 hours, add water, filter out the precipitated crystals, wash with ethanol, and filter; the crude product is purified by silica gel column chromatography using dichloromethane / n-heptane as the mobile phase to obtain compound 1 (6.4 g, 43%) as a white solid, m / z=698.32[M+H]+.

[0126] Synthesis example 2:

[0127] Synthesis of intermediate b-1:

[0128]

[0129] 1,2-Dibromo-3-chlorobenzene (80.0 g, 298.7 mmol), phenylboric acid (36.5 g, 298.7 mmol), tetrakis(triphenylphosphine)palladium (6.9 g, 6.0 mmol), potassium carbonate (103.2 g, 746.7 mmol), tetrabutylammonium bromide (19.2 g, 59.7 mmol) were added to a flask, and a mixed solvent of toluene (600 mL), ethanol (150 mL) and water (150 mL) was added. Under nitrogen protection, the temperature was raised to 80°C, and the temperature was maintained and stirred for 18 hours. The mixture was cooled to room temperature and stirring was stopped. The reaction solution was washed with water and the organic phase was separated. The phase was dried over anhydrous magnesium sulfate and the solvent was removed under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography using dichloromethane / n-heptane as the mobile phase to obtain a white solid product intermediate b-1 (42.0 g, 53%).

[0130]

[0131] Add intermediate b-1 (42.0 g, 157.9 mmol) and tetrahydrofuran (300 ml) into a flask. Under nitrogen protection, cool to -78 °C. Add a solution of n-butyl lithium in tetrahydrofuran (2.5 M) (95 mL, 236.9 mmol) dropwise with stirring. After the addition is complete, stir for 1 hour. Add a solution of adamantanone (19.0 g, 126.3 mmol) in tetrahydrofuran (100 mL) dropwise while maintaining -78 °C. After the addition is completed, the mixture is kept warm for 1 hour and then warmed to room temperature. The mixture is stirred for 24 hours. A solution of hydrochloric acid (12M) (26.3 mL, 315.8 mmol) in water (100 mL) is added to the reaction solution and stirred for 1 hour. The mixture is separated and the organic phase is washed with water until neutral. Anhydrous magnesium sulfate is added and dried. The solvent is removed under reduced pressure to obtain a crude product. The crude product is purified by silica gel column chromatography using ethyl acetate / n-heptane to obtain a white solid product intermediate b-2 (25.8 g, 48%).

[0132]

[0133] Add intermediate b-2 (25.8 g, 76.3 mmol) and glacial acetic acid (300 mL) into a flask, slowly add concentrated sulfuric acid (98%) (0.8 mL, 15.3 mmol) in acetic acid (20 mL) under nitrogen protection and stirring at room temperature. After the addition is complete, raise the temperature to 80°C and stir for 2 hours; cool to room temperature, filter the precipitated solid, rinse the filter cake with water and ethanol, and dry to obtain a crude product; purify the crude product by silica gel column chromatography using a dichloromethane / n-heptane system to obtain a white solid intermediate b-3 (20.4 g, 84%).

[0134]

[0135] The intermediate b-3 (7.6 g, 23.7 mmol), 2-chloroaniline (3.2 g, 24.9 mmol), tris(dibenzylideneacetone)dipalladium (0.2 g, 0.2 mmol), 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl (0.2 g, 0.5 mmol), sodium tert-butoxide (3.4 g, 35.6 mmol) and toluene (50 mL) were added into a flask, and refluxed and stirred at 105 ° C for 4 hours under nitrogen protection; cooled to room temperature, the reaction solution was washed with water, separated, the organic phase was washed with water and then dried with anhydrous magnesium sulfate, and the solvent was removed under reduced pressure to obtain a crude product; the crude product was purified by silica gel column chromatography using a dichloromethane / n-heptane system to obtain a white solid intermediate b-4 (7.7 g, 79%).

[0136]

[0137] The intermediate b-4 (7.7 g, 18.7 mmol), palladium acetate (2.1 g, 9.4 mmol), cesium carbonate (24.4 g, 74.9 mmol), tricyclohexylphosphine tetrafluoroborate (6.9 g, 18.7 mmol) and dimethylacetamide (70 mL) were added to a flask, the temperature was raised to 160°C under nitrogen protection, stirred for 12 hours, and then cooled to room temperature. Dichloromethane (300 mL) was added to the reaction solution and then washed with a large amount of water. The obtained organic phase was dried over anhydrous magnesium sulfate, and the solvent was removed under reduced pressure to obtain a crude product; the crude product was purified by silica gel column chromatography using a dichloromethane / n-heptane system to obtain a white solid intermediate b-5 (6.0 g, 85%).

[0138]

[0139] Add 55% sodium hydride NaH (0.92 g, 21.4 mmol) and 100 ml of dehydrated DMF to a three-necked flask replaced with degassed nitrogen, stir under nitrogen flow, and cool to 0°C. Start adding a dehydrated DMF solution of intermediate b-5 (10.0 g, 21.4 mmol) dropwise at 0°C. Stir for 1 hour after the addition, and start adding a DMF solution of 2-(4-bromophenyl)-4,6-diphenyl-1,3,5-triazine (6.6 g, 21.4 mmol) dropwise. After the addition is completed, stir for 3 hours, add water, filter out the precipitated crystals, wash with ethanol, and filter; the crude product is purified by silica gel column chromatography using dichloromethane / n-heptane as the mobile phase to obtain compound 1 (6.4 g, 43%) as a white solid, m / z=694[M+H]+.

[0140] Synthesis example 3

[0141]

[0142] Indole [2,3-A] carbazole (20.0 g, 78.03 mmol), 4-bromo-1,1'-biphenyl (18.18 g, 78.03 mmol), cuprous iodide CuI (2.97 g, 15.60 mmol), 1,10-phenanthroline (5.62 g, 31.18 mmol), potassium carbonate K2CO3 (23.72 g, 171.67 mmol), 18-crown ether-6 (2.06 g, 7.8 0mmol) was added into a three-necked flask, and dried DMF (200mL) solvent was added, and the temperature was raised to 150°C under nitrogen protection, and the temperature was maintained with stirring for 18 hours; cooled to room temperature, and stirring was stopped. The reaction solution was washed with water and the organic phase was separated, and dried over anhydrous magnesium sulfate, and the solvent was removed under reduced pressure to obtain a crude product; the crude product was purified by silica gel column chromatography using dichloromethane / n-heptane as the mobile phase to obtain a white solid product intermediate c-1 (23.9g, 66%).

[0143]

[0144] In a degassed nitrogen-substituted three-necked flask, add 55% sodium hydride NaH (0.92 g, 21.4 mmol) and 100 ml of dehydrated DMF, stir under nitrogen flow, and cool to 0°C, then start adding a dehydrated DMF solution of intermediate c-1 (7.01 g, 21.4 mmol) dropwise at 0°C. After the addition is completed, stir for 1 hour, and after the stirring is completed, start adding a DMF solution of 2-(1-bromotricyclo[4.2.2.03,8]dec-6-yl)-4,6-diphenyl-1,3,5-triazine (9.5 g, 21.4 mmol) dropwise. After the addition is completed, stir for 3 hours, add water, filter out the precipitated crystals, wash with ethanol, and filter; the crude product is purified by silica gel column chromatography using dichloromethane / n-heptane as the mobile phase to obtain compound N3 (6.4 g, 43%) as a white solid, m / z = 685.02 [M+H] +.

[0145] Green light emitting film in the prior art:

[0146] The existing green light emitting film is composed of a main material and a green light doping material, wherein the main material is composed of a P-type material and an N-type material. Generally, the P-type material has a bicarbazole as the core, and the N-type material has a triazine + indolecarbazole as the core. As the molar ratio of the P-type material to the N-type material increases, the relationship between the fluorescence quantum yield of the luminescent film and the molar ratio of the P-type material to the N-type material (P / N ratio) is shown in the figure below: Figure 1 As shown in the figure, for general green light emitting films, the larger the P / N ratio, that is, the smaller the proportion of N-type components, that is, the higher the dispersion of N-type molecules, the larger the PLQY of the main body, and the higher the efficiency of the device. However, the larger the P / N ratio, the significantly higher the device voltage will be. Therefore, in order to balance the RGB voltage, the largest P / N ratio cannot be selected, which will sacrifice some efficiency.

[0147] Embodiments of the green light emitting film in the technical solution of the present invention:

[0148] Examples 1-3, and Comparative Examples 1-3

[0149] A green light emitting film with a thickness of 50nm, comprising:

[0150] Main material: composed of P-type material and N-type material in a molar ratio of 5:5;

[0151] The doping material is a GD material;

[0152] Wherein, in the green light emitting film, the mass percentage of the doping material is 10wt%.

[0153] The preparation method of the green light emitting film is as follows:

[0154] The P-type material and N-type material are placed on the two heating sources of the evaporation machine respectively. By adjusting the evaporation rate, the evaporation rates of the P-type and N-type materials are 0.5A / s:0.5A / s, 0.6A / s:0.4A / s, 0.7A / s:0.3A / s, 0.8A / s:0.2A / s, 0.9A / s:0.1A / s respectively, and the total evaporation thickness is 500nm.

[0155] The P-type materials and N-type materials used in Examples 1-3 and Comparative Examples 1-3 are specifically shown in Table 1 below. It should be noted that the ratios of the P-type materials to the N-type materials in the table refer to molar ratios.

[0156] The fluorescence quantum yield PLQY of the green light emitting thin films prepared in the above-mentioned embodiments and comparative examples was tested using an integrating sphere device, wherein the excitation wavelength was 360 nm. The obtained results are shown in Table 3 below.

[0157] Table 3

[0158] Example film QUR Example 1 P1:N1(5:5):GD(10wt%)(50nm) 0.89 Example 2 P2:N2(5:5):GD(10wt%)(50nm) 0.87 Example 3 P3:N3(5:5):GD(10wt%)(50nm) 0.86 Comparative Example 1 P4: N4 (5: 5): GD (10wt%) (50nm) 0.80 Comparative Example 2 P5:N5(5:5):GD(10wt%)(50nm) 0.78 Comparative Example 3 P6: N6 (5: 5): GD (10wt%) (50nm) 0.82

[0159] It can be seen from the above table that the P-type material and N-type material molecules in the technical solution of the present invention have adamantane structures, which will significantly increase the molecular distance between the P-type material and the N-type material. This is equivalent to the N-type material of the present invention having a higher degree of dispersion under the same P / N ratio conditions, which can further improve the luminous efficiency.

[0160] Embodiment of green organic electroluminescent device:

[0161] Examples 4-8, Comparative Examples 4-8

[0162] Device structure:

[0163] The device structure includes: an indium tin oxide ITO layer on a glass substrate as an anode, a hole injection layer HIL (5-20nm), a hole transport layer (50-200nm), an electron blocking layer (30-60nm), a light-emitting layer EML (20-50nm), a hole blocking layer HBL (2-20nm), an electron transport layer (20-50nm), an electron injection layer (0.5-10nm), and a cathode.

[0164] Specifically: The optional materials for each functional layer of the device are as follows, but not limited to:

[0165] HIL: can be inorganic oxides, such as MoO3, F4-TCNQ, HAT-CN, etc., but not limited thereto;

[0166] HTL: aromatic amine or carbazole materials with hole transport properties, such as NPB, m-MTDATA, TPD, etc., but not limited thereto;

[0167] EBL: aromatic amine or carbazole materials with hole transport properties and electron blocking properties, such as mCBP, Tris-PCz, etc., but not limited thereto;

[0168] HBL: triazine materials with electron transport and hole blocking properties, such as TPBI and BCP, but not limited to these;

[0169] ETL: Materials with electron transport properties, such as B3PYMP, but not limited to these;

[0170] GH: Premix material having a P-type component and an N-type component, the type of the present invention;

[0171] GD: A material having high luminous efficiency, such as Ir(ppy)3, but not limited thereto.

[0172] Preparation of the device: The preparation process of the organic electroluminescent device described in the device embodiment of the present invention is as follows:

[0173] The glass plate with ITO was ultrasonically treated in a cleaning agent, rinsed in deionized water, ultrasonically degreased in an acetone-ethanol mixed solvent, and baked in a clean environment until the water was completely removed;

[0174] Place the ITO glass in a vacuum evaporation equipment and evaporate HIL, HTL, G prime, G-EML, HBL, ETL, EIL and cathode in sequence.

[0175] Among them, in each embodiment and comparative example, the selection of P-type material, N-type material and electron blocking layer material is specifically shown in Table 4 below. It should be noted that the ratio of P-type material to N-type material in the table refers to the molar ratio. The number after GD in the table is the mass percentage of the doping material in the light-emitting layer.

[0176] Table 4

[0177] serial number Electron blocking layer (30nm) Light-emitting layer (30nm) Example 4 G'1 30nm P1:N1(5:5):GD(10wt%)30nm Example 5 G'1 30nm P1: N1 (6: 4): GD (10wt%) 30nm Example 6 G'1 30nm P1:N1(7:3):GD(10wt%)30nm Example 7 G'2 30nm P2: N2 (5: 5): GD (10wt%) 30nm Example 8 G'3 30nm P3: N3 (5: 5): GD (10wt%) 30nm Comparative Example 4 G'4 30nm P4: N4 (5: 5): GD (10wt%) 30nm Comparative Example 5 G'4 30nm P4: N4 (6: 4): GD (10wt%) 30nm Comparative Example 6 G'4 30nm P4: N4 (7: 3): GD (10wt%) 30nm Comparative Example 7 G'5 30nm P5:N5(1:1):GD(10wt%)30nm Comparative Example 8 G'6 30nm P6: N6 (1: 1): GD (10wt%) 30nm

[0178] The IVL and life of the green organic electroluminescent devices (G prime evaporation 30nm, G-EML evaporation 30nm) prepared in the above green organic electroluminescent device embodiments and comparative examples were tested. 2 The results are shown in Table 5 below.

[0179] Table 5

[0180]

[0181]

[0182] Note: Take the data of comparative example 1 as reference, and set its voltage, efficiency and life data to 100%.

[0183] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A green organic electroluminescent device, characterized in that: comprising a light-emitting layer, wherein the light-emitting layer comprises a host material; The main material includes P-type material and N-type material; wherein, At least the N-type material comprises a compound having a structural formula shown in Formula I and / or Formula II below: in: R0 is selected from C or N; R3, R4 and R a are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl, and R3, R4 and R a At least one of them is adamantyl or an adamantyl derivative; L3 is selected from a single bond, adamantyl, C6 to C30 aryl or heteroaryl; The P-type material has a structure shown in the following formula III: in: R1 and R2 are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl; L1 and L2 are each independently selected from a single bond, a C6 to C30 aryl or heteroaryl group; n1 and n2 are independently selected from 0 or 1.

2. The green organic electroluminescent device according to claim 1, characterized in that: The specific structure of the compound having the structural formula shown in Formula I or Formula II is one of the following formulas: in: R3, R4, and R5 are each independently selected from adamantyl, adamantyl derivative, C6 to C30 aryl or heteroaryl, and at least one of R3, R4, and R5 is adamantyl or adamantyl derivative; R6, R7, and R8 are each independently selected from C6 to C30 aryl or heteroaryl; L3 and L4 are each independently selected from a single bond, an adamantyl group, a C6 to C30 aryl group or a heteroaryl group.

3. The green organic electroluminescent device according to claim 1 or 2, characterized in that: The adamantyl derivative is an adamantyl substituted with a C6 to C30 aryl or heteroaryl group.

4. The green organic electroluminescent device according to claim 1 or 2, characterized in that: The C6 to C30 aryl groups, when present at each occurrence, are independently selected from phenyl, biphenyl, triphenylene or fluorenyl; and / or The C6 to C30 heteroaryl group, at each occurrence, is independently selected from dibenzofuranyl or thienyl.

5. The green organic electroluminescent device according to claim 4, characterized in that: The specific structure of the compound is one of the following formulas:

6. The green organic electroluminescent device according to claim 1, characterized in that: The molecular distance between the P-type material and the N-type material is above.

7. The green organic electroluminescent device according to claim 1, characterized in that: The P-type material has a structure shown in one of the following formulas III-1 to III-3:

8. The green organic electroluminescent device according to claim 1, characterized in that: The organic electroluminescent device further comprises an electron blocking layer disposed adjacent to the light-emitting layer, wherein the material of the electron blocking layer has a structure shown in the following formula IV: Among them, R9, R 10 , R 11 Each is independently selected from one of adamantyl, spirofluoreneadamantyl, fluorenyl, dimethylfluorenyl, diphenylfluorenyl, spirofluorenyl, phenyl, biphenyl, diphenylfuranyl, thienyl, spirooxy and thioxanthenyl.

9. The green organic electroluminescent device according to claim 1, characterized in that: The HOMO energy level of the N-type material is 5.4-5.8 eV, and the LUMO energy level is 2.2-2.6 eV; The HOMO energy level of the P-type material is 5.3-5.6 eV, and the LUMO energy level is 2.0-2.4 eV; The T1 energy level of the N-type material is 2.2-2.8 eV, and the T1 energy level of the P-type material is 2.5-3.1 eV; and The difference between the T1 energy level of the P-type material and the T1 energy level of the N-type material is more than 0.1 eV.

10. The green organic electroluminescent device according to claim 8, characterized in that: The HOMO energy level of the material of the electron blocking layer is 5.3-5.7 eV, and the LUMO energy level is 2.2-2.7 eV; The T1 energy level of the material of the electron blocking layer is 2.5-3.1 eV; and The T1 energy level of the material of the electron blocking layer is greater than the T1 energy level of the P-type material.

11. The green organic electroluminescent device according to claim 1, characterized in that: The glass transition temperature of the N-type material is 80-140° C., the glass transition temperature of the P-type material is 80-140° C., and the difference between the glass transition temperature of the N-type material and the glass transition temperature of the P-type material is less than 30° C.

12. The green organic electroluminescent device according to claim 1, characterized in that: The molar ratio of the P-type material to the N-type material is 5:5-7:

3.

13. A display device, characterized in that: The invention comprises the green organic electroluminescent device as claimed in any one of claims 1 to 12.

Citation Information

Patent Citations

  • Organic electroluminescent device

    CN109994636A

  • Organic light-emitting device and electronic device

    CN113380954A